Measuring and analyzing the impact of some macroeconomics variables on the foreign trade in China during the period between 2000 - 2019 (Entrepreneurship Journal for Finance and Business, 2021)
The aim of the research is to study the impact of some macroeconomic variables in China represented by investment with local capital , foreign investment, Gross Domestic Products(GDP) , rate of inflation and economic growth rate and the exchange rate in dollars in foreign trade represented by exports and imports, (Industry and services) for the period 2000-2019, by adopting standard analysis where the gradual multiple linear regression was analyzed of the role of some variables in the economy in the growth of Foreign Trade Ministry in China during the time period above. The research reached the following results: (1)-There is a significant indicative role for the two variables of investment in domestic capital and foreign investment in the development of foreign trade movement. (2)-There is no significant indicative role for the exchange rate variation, the rate of inflation, and economic growth in the development of foreign trade. (3)-There is a significant indicative role for the variable (GDP )in the development of the movement of Foreign trade in China, if it is adapted independently away from the suggested changes in the research, as its impact is clear on China imports and then exports.(4)-There is an investment increase in domestic capital and foreign trade movement in China.(5)-There is relative stability in foreign investment.(6)-There is a decline in the rate of economic growth to the (GDP) between 2000- 2019 as well as the exchange rate of the dollar against the Chinese Yuan. And the research presented several proposals, including the importance of studying the impact of foreign trade from exports, imports, by sector: industrial, agricultural, medical, technology, and the role of the foreign trade in China in the world countries’ economies, especially the European Union and UAS.